Proclus of Constantinople and the Cult of the Virgin in Late Antiquity : Homilies 15, Texts and Translations. - Constas, Nicholas. (Vigiliae Christianae, Supplements, 2003)
Proclus of Constantinople was an outstanding pulpit orator who established the rhetoric and rationale for the Byzantine devotion to the Mother of God. In this book, the critical editions of Proclus' most celebrated Marian sermons (Homilies 1-5) provide the point of departure for a far-reaching study of the rise of the Virgin's cult in Late Antiquity. The homilies are supported by a historical introduction to the life and work of Proclus, situating him within the larger religious culture of fifth-century Constantinople. Richly documented chapters explore the symbolism of the incarnation and virgin birth, including the notion of virginal \'conception through hearing,\' and the image of Mary's womb as a textile loom wich weaves a veil of flesh the bodiless divinity.